2020
DOI: 10.1371/journal.pcbi.1007764
|View full text |Cite|
|
Sign up to set email alerts
|

StanDep: Capturing transcriptomic variability improves context-specific metabolic models

Abstract: Diverse algorithms can integrate transcriptomics with genome-scale metabolic models (GEMs) to build context-specific metabolic models. These algorithms require identification of a list of high confidence (core) reactions from transcriptomics, but parameters related to identification of core reactions, such as thresholding of expression profiles, can significantly change model content. Importantly, current thresholding approaches are burdened with setting singular arbitrary thresholds for all genes; thus, resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 58 publications
1
48
0
Order By: Relevance
“…Several interferon-related genes ( IFI6 , IFI27 ) follow a similar pattern in plasmablasts in the scRNA-seq data from cohort 1 and 2, corroborating the suppression of IFN signalling by severe SARS-CoV-2 infection in plasmablasts themselves. Of note, we found that the COVID-19 plasmablasts were predicted to be highly metabolically active in a systems biology modelling approach 77 , beyond their expected upregulation of an unfolded protein response 92 . Among the pathways from the transcriptional pattern-derived model, we identified glycolysis and amino acid catabolism to be transiently activated, while NAD + energy metabolism, vitamin B2 and several transport processes were specifically inhibited at the critical peak of the disease in plasmablasts, when compared to other B cell subpopulations.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Several interferon-related genes ( IFI6 , IFI27 ) follow a similar pattern in plasmablasts in the scRNA-seq data from cohort 1 and 2, corroborating the suppression of IFN signalling by severe SARS-CoV-2 infection in plasmablasts themselves. Of note, we found that the COVID-19 plasmablasts were predicted to be highly metabolically active in a systems biology modelling approach 77 , beyond their expected upregulation of an unfolded protein response 92 . Among the pathways from the transcriptional pattern-derived model, we identified glycolysis and amino acid catabolism to be transiently activated, while NAD + energy metabolism, vitamin B2 and several transport processes were specifically inhibited at the critical peak of the disease in plasmablasts, when compared to other B cell subpopulations.…”
Section: Discussionmentioning
confidence: 83%
“…As metabolically active cells, plasmablasts have been reported to modulate immune responses by serving as a nutrient sink 76 . Thus, we next applied our cell-specific metabolic model to the expression data of cell-types of interest, using a constraint-based method through the reconstruction of the metabolic state of individual cells from scRNA-seq data core reactions 77 . Plasmablasts found in inflammatory states of the disease trajectory (pseudotimes 1-4) were associated with metabolic hyperactivity, which was reduced only upon recovery to the state of healthy subjects (Supplementary Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, selecting a threshold value to consider ligands and receptors as expressed can affect the number of false positives and negatives 9 . In this regard, different values could be explored to infer the presence of biologically active protein, as previously addressed 92,93 . Moreover, other approaches such as using expression products to compute the usage of a ligand-receptor pair may also help 10 , but further adaptations should be done to use it with our Bray-Curtis like score.…”
Section: Discussionmentioning
confidence: 99%
“…We use this threshold-based method for the classification of reactions based on gene expression levels because of its simplicity and widespreadness, but other methods could be used instead, for example StanDep [ 44 ] or Barcode [ 45 ] (for Affymetrix microarray data). Changing the method changes the set of optimal solutions to the problem, but does not eliminate the problem associated with the enumeration.…”
Section: Methodsmentioning
confidence: 99%